(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know the effect of the effectiveness of educational comic story in the collection and contemplative thinking In chemistry for second grade students at middle and through the verification of hypotheses Elsafreeten following cases: 1-There is no difference statistically significant at the level (0.50) between the average scores of the experimental group And taught according to the educational story mode and an average degree of control group and taught according to the traditional way in the collection of chemistry second grade average. 2- There is no difference statistically significant at the level (0.50) between the ability of students in the experimental group and control group on reflective thinking. Choice of experimental design with a partial control groups (experimental and control) that control each other . The number of the respondents (50), a student at the Hariri High School for Girls, represented the experimental group (25 students) and taught according to the educational story, and (25) students studying in accordance with the normal way. The two groups of equal Search variables(intelligence test- Age-pre- scores) Promising achievement of an objective multiple choice test consisting of four alternatives (20) items Verified virtual test sincerity of submitting it to the experts and arbitrators in the field of education and teaching methods and evaluation and measurement The sincerity of content through the preparation of the map test was bringing stability account (84%) were difficult to find and the ease and effectiveness of alternatives to the paragraphs of the test plants. To investigate, the second goal of the search was adopted Isik scale and Wilson speculative to think with the amendment of some paragraphs Statistics regarding the educational content of the story and content to be explained Ensure that the scale (30), paragraph three alternatives (Awavq- not Awavq- I do not know) were checking the veracity of the scale submitting it to the experts and arbitrators in the field of education and teaching methods and evaluation and measurement was stability coefficient was calculated as the amount (83%). Data processing has statistically " using theT- test, and the results showed superiority of the experimental group that studied according to educational storyboard to the control group, who studied in accordance with the normal way of thinking and achievement test contemplative. Thus, the researchers recommend using educational story in the teaching of science and suggest further studies of the different stages of material.